Hush-hush - Woods, Stuart (Woods, Stuart. Stone Barrington novel., 2020)
"Stone Barrington is settling in for some downtime in New York City when an anonymous enemy makes himself known. This nameless foe's threats hit close to home, and before Stone can retaliate, the fearsome messages turn into very real consequences. With the help of old friends--and a lovely new tech-savvy acquaintance--Stone sets out to unravel the fatal agenda. But as the web of adversaries expands, Stone realizes that no place is safe, and he'll have to flush out the mastermind before he and those closest to him are silenced for good..."--